⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ f ( x ) = x + ∫ 0 1 t ( x + t ) f ( t ) d t g ( x ) = a ( 6 2 3 f ( x ) ) 2 + b ( 6 2 3 f ( x ) ) + c
Let f and g be two functions as defined above, where a , b and c are non-zero constants and the coefficients of x 2 , x and 1 in the function g ( x ) are equal. Find a b + c − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = x + ∫ 0 1 t ( x + t ) f ( t ) d t f ( x ) = x + x ∫ 0 1 t ∗ f ( t ) d t + ∫ 0 1 t 2 f ( t ) d t
Thus f ( x ) is a linear function
Let f ( x ) = p x + q
p = 1 + ∫ 0 1 t f ( t ) d t q = ∫ 0 1 t 2 f ( t ) d t
And,
t f ( t ) = p t 2 + q t ∴ p = 1 + ∫ 0 1 ( p t 2 + q t ) d t 4 p = 3 q + 6 ⋯ ( E q n 1 )
Also,
q = ∫ 0 1 ( p t 3 + q t 2 ) d t ∴ 3 2 q = 4 p p = 3 8 q ⋯ ( E q n 2 )
On solving, we get-
f ( x ) = 2 3 4 8 x + 2 3 1 8 ∴ 6 2 3 f ( x ) = 8 x + 3
Hence,
g ( x ) = a ( 8 x + 3 ) 2 + b ( 8 x + 3 ) + c g ( x ) = 6 4 a x 2 + x ( 8 b + 4 8 a ) + 9 a + 3 b + c
The coefficients of x 2 , x and 1 are are equal.
Thus we finally get, b = 2 a and c = 4 9 a , and-
a b + c − 1 = a 4 9 a + 2 a − 1 = 5 0